Evaluation of resources for analyzing drug interactions - Risha I. Patel; Robert D. Beckett (Journal of the Medical Library Association, 2017)
Objective: The research sought to evaluate seven drug information resources, specifically designed for analyzing drug interactions for scope, completeness, and ease of use, and determine the consistency of content among the seven resources.